Optimization of Investigations by the Special Criminal Unit of Satreskrim Karanganyar Resort for Disclosing Online Criminal Actions - Nugroho, Bima Argi (Advances in Police Science Research Journal, 2024)
The author raises this final project research departing from the increasing number of online fraud cases in the Karanganyar Police jurisdiction. Of these high cases, none of the cases could be resolved, all cases stopped at the investigation stage. That way it can be said that there are problems in the form of investigations by the Karanganyar Police Criminal Investigation Unit into criminal acts of online fraud that have not been optimal. The problems in this final project are (1) How is the SDO of the Satreskrim Special Unit of the Karanganyar Police in carrying out investigations of online fraud crimes, and (2) How does the work system of the Karanganyar Police Satreskrim Special Unit in conducting investigations of online fraud crimes This final project research uses a qualitative approach and uses POAC Management Theory, Organizational Resource Theory, and SWOT Analysis Theory, as well as optimization concepts, investigative concepts, disclosure concepts, and online fraud concepts. The results of the study found that the investigation carried out by the Criminal Investigation Unit was still not optimal. There are several reasons, but the most important is because of three things, namely the lack of quality and quantity of personnel, the lack of facilities and infrastructure, and the absence of an investigative method capable of uncovering criminal acts of online fraud. From this discussion, the author provides several solutions to the problem, namely giving members the opportunity to gain knowledge through formal or non-formal education in the field of cyber, requesting expert technical assistance for investigation, utilization and maintenance of owned infrastructure, applying for Alsus loans to Bareskrim Polri for investigations, using Bag MC Bareskrim Polri, asking PPATK for information assistance, making investigation flow charts, disposition cases according to the competence of members, contacting perpetrators so that they are provoked using active numbers or links made by investigators and making direct inspections as a means of control. The author also suggests to the leadership to procure special tools for Direction Finder and Alsus Surveillance, proposes positive cooperation between Satreskrim and Lapas, proposes for the Polda HR to add personnel to the Pidsus Unit, and add members in the form of civil servants or from the private sector for IT assistance.